ENGLISH IN PRESCHOOL CURRICULUM: A DESCRIPTIVE STUDY OF THE TEACHING OF ENGLISH AS AN INTRA-SCHOOL CURRICULUM IN A PRESCHOOL IN BANDUNG - Rachmawati, Yuli; Al-Munawwarah, Sophia Fithri; Aini, Wildan Nurul; Susilawati, Susilawati (Universitas Pendidikan Indonesia, 2014)
In this era, the importance of English leads people to introduce English education even in preschools. English education for preschoolers isbelieved to help fosterchildren’s language and cognitive developments. However, to achieve this benefit, a sound curriculum is required.Since creating a sound English curriculum is not an easy thing to do, a careful examination on English in the preschool curriculum needs to be performed. This study therefore aims to find out the goals of integrating English as an intra-school curriculum in a preschool in Bandung and the teacher’s attempts to achieve these goals in terms of four basic components of curriculum taken fromCayadong (2011) and Tyler (Posner,1992); the objectives, the materials, the methods and the assessments. A descriptive study using a document analysis, an interview and an observation as the data collection techniques was employed. The finding showed that English was integrated to help children to be able to communicate using English in school and family context in a simple language. Theme-based teaching and learning using drilling and total physical response (TPR) as methods were conducted to achieve the goals. Meanwhile, to make sure of the goals attainment, students wereassessed by using observations and tests.